Investigation into minimal-cutting-fluid application in high-speed milling of hardened steel using carbide mills - Thepsonthi, T.; Abd Shukor, Mohd Hamdi; Mitsui, K. (2009)
Applying cutting fluid in a metal-cutting process can reduce the rate of tool wear and improve surface quality. However, cutting fluid has negative effects on the working environment and the use of cutting fluid also increases the total production cost. Therefore, there is a need to reduce the use of cutting fluid during machining. To serve that purpose, a minimal-cutting-fluid technique was studied. In the present work the cutting fluid was applied in a form of a high-velocity, narrow, pulsed jet at a rate of 2 ml/min. The performance of machining with pulsed-jet application was studied in high-speed milling of hardened steel, compared to dry machining and machining with flood application. The results clearly show that compared to dry machining and machining with flood application, machining with pulsed-jet application lowers cutting forces, reduces tool wear, increases tool life, and improves surface roughness, especially when machining with high cutting velocity. Moreover. the amount of cutting fluid consumed at the rate of 2 ml/min is a drastic reduction compared to flood application. Also, no harmful oil mist is generated during the pulsed-jet application. In conclusion, the pulsed-jet application can be applied to milling process of hardened steel using ball end mills; it reduces the negative effects to the environment, improves machining performances, and consequently reduces total production cost. (C) 2008 Elsevier Ltd. All rights reserved.